The phenomenon of electronic extortion and prevention methods Sociological reading and theoretical opinions - - Said ZIUOCHE (Social Sciences Journal, 1970)
Cyberextortion are relatively new phenomena where she didn't appear until the emergence andexpansion of the Internet, and with the advent of communication became increasingly famousphenomenon affecting Algerian society without exception classes, this phenomenon has takenseveral dimensions, where the most important occurrence of theft and rapes, and we said that allsocial institutions the tasks assigned to them under the protection and prevention of risk ofCyberextortion in full coordination with the various security devices that never slackened insurveillance, research and investigation From these criminals, while remaining methods ofprevention from falling victim to the racketeer of major foundations that one must follow to ensureprotection and security